A Hard EM algorithm for prediction of the cured fraction in survival data - Kosovalić, Nemanja; Barui, Sandip (Computational statistics, 2022)
In clinical studies, survival analysis is a well known technique to analyze time to event data with the assumption that every subject in the study will encounter the event of interest. With recent advancements in the drug development industry, a fraction of subjects may not face the event and are considered as immune or cured. However, due to the finite study period, full knowledge of subjects who are immune is usually not known and hence, can be considered as missing. We develop a novel semi-parametric algorithm to address this problem by minimizing a suitable loss function, which incorporates the missing data and generates cure indicators for the censored individuals. We prove the existence of a global minimizer for the loss function and establish some asymptotic properties, demonstrate via numerical experiments that under appropriate circumstances, our approach performs better than simpler alternatives, and use this algorithm to estimate lifetime parameters and the overall survivor function.